(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Osteoporosis and scoliosis are encountered concurrently. Scoliosis predisposes to osteoporosis but degenerative scoliosis could falsely elevate lumbar bone mineral density measurement leading to discordance. This study was conducted to determine the prevalence of discordance between lumbar spines and hip bone mineral density in patients with lumbar scoliosis and to evaluate the risk factors of discordance. The prevalence of osteoporosis and discordance was determined as major and minor discordance. Old age, age at menopause, sex and BMI were considered as possible risk factors for discordance and were used in multivariate logistic regression analysis. Discordance between lumbar spines and hip was found in 55 (78.6 %) patients and among them major and minor discordance of T-scores were seen in 18 (25.7%) and 37 (52.9%) respectively. Concordance of T scores was seen in 15 (21.4%). In multivariate logistic regression analysis female sex, age older than 60 years and BMI less than 30 kg/m2 was identified as risk factors for T-score discordance. In lumbar scoliosis the overestimation of lumbar spine may lead to diagnostic dilemma, whereas hip DEXA appears to be more reliable in these cases. In such cases it is in the jurisdiction of the physician to look for possible underlying causes of discordance of T score. Bangladesh J. Nuclear Med. 18(2): 121-124, July 2015